Uji Keefektifan Rizobakteri dalam Menghambat PertumbuhanJamurColletotrichum spp. Penyebab Antraknosa pada Cabai Merah (Capsicum annuum L.) - SRIYANTI, NI LUH GEDE; SUPRAPTA, DEWA NGURAH; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.1, Januari 2015, 2015)
ABSTRACT Effectiveness of Rhizobacteria to Inhibit the Growth of Colletotrichum spp. the Cause of Antracnose on Red Chilli ( Capsicum annuum L.) Colletotrichum spp . is one of pathogenic fungi that cause significant losses on red chilli. The use of rhizobacteria is considered as an alternative to control the growth of the fungus. The use of bio agent control is considered as selective and environmentally friendly. The aim of this study is to know the effectiveness of rhizobacteria and their filtrates in suppressing the growth of Colletotrichum spp . Results of this study showed that treatment with Pseudomonas fluorescens isolate TBZA on PDA medium could suppress the growth of Colletotrichum spp . by 94% when compared to control 14 days after inoculation. Treatment with filtrate of P. fluorescens isolate TBZA could suppress the anthracnose disease indicated by the lower disease incidence viz 32%. It is necessary to conduct further experiment under field condition to know the effectiveness of P. fluorescens isolate TBZA to suppress the growth of Colletotrichum spp . In addition isolation and identification of antifungal compounds in the filtrate is necessary to be done. Keywords: rhizobacteria, biologicalagents, and Colletotrichum spp .
Keywords: rhizobacteria, biologicalagents, Colletotrichumspp